2021
DOI: 10.1083/jcb.201907183
|View full text |Cite
|
Sign up to set email alerts
|

FIT2 organizes lipid droplet biogenesis with ER tubule-forming proteins and septins

Abstract: Lipid droplets (LDs) are critical for lipid storage and energy metabolism. LDs form in the endoplasmic reticulum (ER). However, the molecular basis for LD biogenesis remains elusive. Here, we show that fat storage–inducing transmembrane protein 2 (FIT2) interacts with ER tubule-forming proteins Rtn4 and REEP5. The association is mainly transmembrane domain based and stimulated by oleic acid. Depletion of ER tubule-forming proteins decreases the number and size of LDs in cells and Caenorhabditis elegans, mimick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 66 publications
0
32
0
Order By: Relevance
“…Indeed, it was found that the rate of lipid transfer from the ER to the plasma membrane does not appreciably decrease when vesicular pathways are blocked [ 148 , 149 , 150 , 151 ], indicating that non-vesicular transport alone can sustain the required lipid transfer to the plasma membrane. As MCSs between the ER and other organelles, particularly the plasma membrane, mitochondria, and endosomes [ 73 , 74 , 75 , 76 , 77 , 78 ], preferentially form in the tubular ER network, these findings suggest that lipid transfer occurs primarily in the tubular ER.…”
Section: Morphologymentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, it was found that the rate of lipid transfer from the ER to the plasma membrane does not appreciably decrease when vesicular pathways are blocked [ 148 , 149 , 150 , 151 ], indicating that non-vesicular transport alone can sustain the required lipid transfer to the plasma membrane. As MCSs between the ER and other organelles, particularly the plasma membrane, mitochondria, and endosomes [ 73 , 74 , 75 , 76 , 77 , 78 ], preferentially form in the tubular ER network, these findings suggest that lipid transfer occurs primarily in the tubular ER.…”
Section: Morphologymentioning
confidence: 97%
“…In support of this idea, cells responsible for steroid synthesis, such as adrenal cortical cells, have proportionally more ribosome-free smooth ER [72]. It has also been suggested that membrane contact sites (MCSs) between the ER and other organelles may be more common in the ribosome-free tubular region of the network, particularly those MCSs formed with the plasma membrane, endosomes, lipid droplets and mitochondria [73][74][75][76][77][78]. The MCSs and relevant proteins discussed in this review are shown in Figure 2.…”
Section: Mcss: Lipid Manufacturementioning
confidence: 99%
“…Taken together, these data indicate that the high membrane curvature of ER tubules catalyzes LD biogenesis. [ 15,32–34 ]…”
Section: Membrane Curvature and Ld Biogenesismentioning
confidence: 99%
“…Proteins such as seipin, LDAF1, fat‐inducing transcript (FIT) proteins, and ER shaping proteins such as Pex30 in yeast, MCTP1, MCTP2, and REEP5, in mammalian cells are localized at ER subdomains. [ 14–17 ] These proteins are at ER subdomains where nascent LD markers such as LiveDrop or perilipin 3 are recruited suggesting that LD formation sites could be pre‐determined in the ER membrane. [ 14,16,18 ] Interestingly, extended incubation of cells with oleic acid, an LD inducing growth condition, results in increased size of LDs but not the number, potentially due to limited sites for LD biogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation